The girl with a bracelet [videorecording (DVD)] - Demoustier, Stéphane; Demoustier, Stéphane; Zem, Roschdy; Mastroianni, Chiara, 1972-; Guers, Melissa (Distrib Films, 2020)
A teenage girl comes under investigation and stands trial for the murder of her best friend.